Anatase–Rutile Transition and Photo-Induced Conductivity of Highly Yb-Doped TiO2 Films Deposited by Acid Sol–Gel Dip-Coating Method - Kaezmarek Pedrini, Luiz F. [UNESP]; Santos, Stevan B. O. [UNESP]; Trino, Luciana D.; Scalvi, Luis V. A. [UNESP] (Springer Nature, 2020)
A method to prepare Yb-doped TiO2 is proposed, using titanium isopropoxide and ytterbium oxide. Thin films and powders are produced through the sol–gel technique where the Yb concentrations are 0.01 at.%, 0.02 at.%, 1 at.%, 2 at.% 4 at.% and 8 at.%. The increase in the doping concentration intensifies gradually the sample transparency for the whole observed spectrum and reaches the transparency degree of the undoped sample with the highest concentration of ytterbium. By means of x-ray diffraction (XRD) we find that the solution’s pH leads to the formation of a rutile structure which is compensated for by lanthanide doping, inhibiting the anatase–rutile phase transformation. Then, the XRD profile depends on the Yb concentration, being mostly anatase for undoped and highly (8 at.%) doped samples, with mixed ratios of these two phases in other concentrations. Maintaining an acid solution leads to fewer intergrain defects in the rutile structure contributing to higher conductivity. Photo-induced investigation of 8 at.% Yb-doped thin film, using several light sources leads to distinct behavior concerning the excitation of intra-bandgap states and/or electron–hole pairs. This result helps to understand the electronic transport in Yb-doped TiO2 and shows that devices based on its conductivity may have improved performance by irradiation with controlled light energy.
Keywords: phase transition; photoconductivity; Titanium dioxide; ytterbium